The Community Aspect of Kant’s Virtuous Circle Between Ethics and Politics - Martinazzo, Nicole (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article examines the interplay between the moral and the political in Kant’s thought the concept of community. In doing so, it draws an analogy between two relations: that between the ethical and the political community, and that between moral and political progress. Through this analogy, I argue (i) that Kant grants logical precedence to political progress, (ii) that there is a virtuous circle between moral and political progress, and (iii) that forming a community is both a duty and a human predisposition.